2013
DOI: 10.1080/19393555.2014.891281
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Analysis of Ring Oscillator PUFs on 60 nm Altera Cyclone FPGAs

Abstract: Ring Oscillator (RO) physically unclonable functions (PUFs) on field programmable gate arrays (FPGAs) have drawn much attention in recent years. Making each FPGA uniquely identifiable, they allow for protection of intellectual property (IP) or generation of secret encryption keys. Their implementation has been widely discussed, but most experiments have been conducted on Xilinx platforms. In this paper, we report the statistical results from an analysis spanning 20 Cyclone IV FPGAs with 60 nm technology. We pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
1
17
1
Order By: Relevance
“…Although the reliability improves significantly with the temporal majority voting, it requires repeating PUF measurements which is, compared to our solutions, takes much longer due to the measurement time of the oscillators. Recent work also complies with our results and shows that on similar Altera FPGAs, the quality of RO based PUFs can change drastically and can have an anomalous characteristics [23]. However, the typical quality metrics for RO-PUFs on Xilinx FPGAs are much better than what is achieved on Altera FPGAs [13].…”
Section: Advanced Metrics Of Quality For Authentication Identifierssupporting
confidence: 89%
“…Although the reliability improves significantly with the temporal majority voting, it requires repeating PUF measurements which is, compared to our solutions, takes much longer due to the measurement time of the oscillators. Recent work also complies with our results and shows that on similar Altera FPGAs, the quality of RO based PUFs can change drastically and can have an anomalous characteristics [23]. However, the typical quality metrics for RO-PUFs on Xilinx FPGAs are much better than what is achieved on Altera FPGAs [13].…”
Section: Advanced Metrics Of Quality For Authentication Identifierssupporting
confidence: 89%
“…The structure is equipped with a CRP generation process, where demultiplexers and multiplexers are placed before and after ROs, respectively. Therefore, the unequal route distances from ROs to counters caused inaccuracy in counting RO pulses, which were identified as locking phenomena [26,27] or jitter noise [28]. Meanwhile, this work proposes a modified RO-PUF structure that connects ROs directly to counters (no intermediary circuit between the ROs and the counters), as shown in Figure 1.…”
Section: Proposed Ro-pufmentioning
confidence: 99%
“…According to previous works, three-stage RO is less stable [28,[32][33][34]. The frequencies of ROs are varied, from 120 MHz to 200 MHz, leading to a standard deviation of 11.3 MHz, which is relatively high compared to the ROs, which are realized using higher stages, around 1 MHz [32,34].…”
Section: Ro Implementationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that the RO-PUF is the best candidate for FPGAs (eg. [18], [19], [20], [21]). Unfortunately, the RO-PUF has a security problem: it can be cloned using electromagnetic analysis [22] or RO cells can be locked using electromagnetic injections [23].…”
Section: Introductionmentioning
confidence: 99%